Research advancements in the neurological presentation of flaviviruses. (12th December 2018) - Chen, Tingting; He, Xiaoen; Zhang, Peiru; Yuan, Yawen; Lang, Xinyue; Yu, Jianhai; Qin, Zhiran; Li, Xujuan; Zhang, Qiwei; Zhu, Li; Zhang, Bao; Wu, Qinghua; et al.
Summary: Owing to the large‐scale epidemic of Zika virus disease and its association with microcephaly, properties that allow flaviviruses to cause nervous system diseases are an important area of investigation. At present, although potential pathogenic mechanisms of flaviviruses in the nervous system have been examined, they have not been completely elucidated. In this paper, we review the possible mechanisms of blood‐brain barrier penetration, the pathological effects on neurons, and the association between virus mutations and neurotoxicity. A hypothesis on neurotoxicity caused by the Zika virus is presented. Clarifying the mechanisms of virulence of flaviviruses will be helpful in finding better antiviral drugs and optimizing the treatment of symptoms.